The use of banana peel as feed to increase growth of earthworms (Lumbricus rubellus) - I Wayan Merta; Ahmad Raksun (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
Research on using banana peels as feed to increase the growth of Lumbricus rubellus has been carried out. This study aims to determine: (1) the effect of different doses of banana peel pulp on feed on the growth of earthworms (Lumbricus rubellus), (2) the best dose of banana peel pulp to increase the growth of earthworms. This research is a one-factor study. The research was carried out with five levels of treatment and five replications. The doses of banana peel pulp are 0 ml, 250 ml, 500 ml, 750 ml, and 1000 ml. The parameters of the growth of earthworms measured were the addition of the number of individuals and the addition of the weight of the earthworm population. The research data were analyzed by analysis of variance. The research results show that: (1) the difference in the dose of banana peel pulp significantly affected the increase in the number of individuals and the weight of the earthworm population; (2) the addition of 1000 ml of banana peel pulp resulted in the highest number of individuals and the heaviest population weight compared to other treatment doses.